Selection of Reference Genes for Expression Analysis in Chinese Medicinal Herb Huperzia serrata - Yang, Mengquan; Wu, Shiwen; You, Wenjing; Jaisi, Amit; Xiao, Youli (Frontiers in Pharmacology, 2019)
Huperzine A (HupA) is a powerful and selective inhibitor of acetylcholinesterase. It has attracted widespread attention endangering the ultimate plant sources of Lycopodiaceae family. In this study, we used Huperzia serrata, extensively used in Traditional Chinese medicine (TCM), a slow growing vascular plant as the model plant of the Lycopodiaceae family to develop and validate the reference genes. We aim to use gene expression platform to understand the gene expression of different tissues and developmental stages of this medicinal herb. Eight candidate reference genes were selected based on RNA-seq data and evaluated with qRT-PCR. The expression of L/ODC and cytochrome P450s genes known for their involvement in lycopodium alkaloid biosynthesis, were also studied to validate the selected reference genes. The most stable genes were TBP, GAPDH, and their combination (TBP + GAPDH). We report for the first time the reference gene of H. serrata’s different tissues which would provide important insights into understanding their biological functions comparing other Lycopodiaceae plants and facilitate a good biopharming approach.